Enhancing Human Development Through CSR Initiatives: A Case Study of PT Adaro Indonesia's Impact on Villages in Mining Operations - Aan Nurhadi; Firmansyah; Yuri Budi Sujalmi; Heriyanto Andilolo; Lenie Marlinae; Tien Zubaidah; Muhammad Ratodi (International Journal of Educational and Life Sciences, 2023)
From 2018 through 2023, this study examines how PT Adaro Indonesia's CSR programs affected villages in their major operations area, concentrating on HDI metrics like life expectancy, education, and living standards in South and Central Kalimantan. In 65 villages, 78% scored a high Human Development Index (HDI) and 22% a medium HDI. In comparison, 38% of villages had an HDI fall, while 62% saw an increase. In 98% of communities, CSR programs in education, healthcare, social and cultural advancement, environmental sustainability, and economic progress raised the consumption index (CI). These studies show that PT Adaro Indonesia's CSR activities improve community well-being, including healthcare, education, economic empowerment, and community-based projects, benefiting local populations. This research is crucial for mining operation planning.